INTERAKSI SENYAWA AKTIF DARI Aegle marmelos CORREA SEBAGAI ANTI INFLAMASI DENGAN RESEPTOR COX-1 DAN COX-2 - Dani Dwi Agistia; Hari Purnomo; Maulana Tegar; Agung Endro Nugroho (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
The compounds in Aegle marmelos have an activity as anti inflammation. The objective of this study is to evaluate six active compounds in Aegle marmelos Correa, (E,R)- Marmin, skimmianine, (S)-aegeline, aurapten, zeorin, and dustanin as anti inflammation to the COX-1 and COX-2 as target receptors. Method: Molecular docking was done with PLANTS. Ligand preparation used MarvinSketch, and protein preparation was done by using YASARA. The result was marmin, skimmianine, aegeline, aurapten, zeorin, and dustanin have interaction with Arg120, tyr 355, and Ile 523 in COX-1 and Ser353, Arg 513, and Ser 530 in COX-2. Based on the result of molecular docking, active compounds in Aegle marmelos Correa have potency as anti inflammation agent.